Grammar as A Tool for Enhancing Speaking Competence: A Narrative Inquiry into Students’ Experiences - Ulvatun Nisa (Linguapedia, 2025)
This study explores how students perceive and use grammar to improve their English Speaking abilities. Using a qualitative narrative approach, data were collected through semi-structured interviews and participatory observation. Thematic analysis shows that a solid understanding of grammar helps students form clear sentences, maintain consistent tenses, ensure coherence, and increase their confidence in speaking. However, grammar alone does not guarantee fluency, as students face challenges such as limited processing time, spontaneous speech without considering structure, and interference from their native language. The study also highlights the importance of a supportive learning environment, the integration of technology, and quality instruction in effectively applying grammar in speaking contexts. These findings emphasize the need for a more contextual, communicative, and supportive educational approach to help students meaningfully use grammar for enhancing their speaking skills.